Echoes of the great catastrophe - League, Paddy, 1979- (Ann Arbor)
xvii, 182 sayfa
Keywords: “Echoes of the Great Catastrophe: Re-sounding Anatolian Greekness in Diaspora explores the legacy of the Great Catastrophe-the death and expulsion from Turkey of 1.5 million Greek Christians following the Greco-Turkish War of 1919-1922-through the music and dance practices of Greek refugees and their descendants over the last one hundred years. The book draws extensively on original ethnographic research conducted in Greece (on the island of Lesvos in particular) and in the Greater Boston area, as well as on the author's lifetime immersion in the North American Greek diaspora. Through analysis of handwritten music manuscripts, homemade audio recordings, and contemporary live performances, the book traces the routes of repertoire and style over generations and back and forth across the Atlantic Ocean, investigating the ways that the particular musical traditions of the Anatolian Greek community have contributed to their understanding of their place in the global Greek diaspora and the wider post-Ottoman world. Alternating between fine-grained musicological analysis and engaging narrative prose, it fills a lacuna in scholarship on the transnational Greek experience.“ --